2010
DOI: 10.1577/m09-182.1
|View full text |Cite
|
Sign up to set email alerts
|

The Bioeconomic Impact of Different Management Regulations on the Chesapeake Bay Blue Crab Fishery

Abstract: The harvest of blue crabs Callinectes sapidus in Chesapeake Bay declined 46% between 1993 and 2001 and remained low through 2008. Because the total market value of this fishery has declined by an average of US $ 3.3 million per year since 1993, the commercial fishery has been challenged to maintain profitability. We developed a bioeconomic simulation model of the Chesapeake Bay blue crab fishery to aid managers in determining which regulations will maximize revenues while ensuring a sustainable harvest. We com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…The Chesapeake Bay is the largest source of blue crabs in United States, accounting for about 50% of the nation's blue crab harvest (Miller et al 2011). Economically, blue crab is the largest commercial fishery in Chesapeake Bay (Miller et al 2011) with a market value of US$46-103 million annually (Bunnell et al 2010).…”
Section: Background On the Chesapeake Bay Blue Crab Fisherymentioning
confidence: 99%
See 2 more Smart Citations
“…The Chesapeake Bay is the largest source of blue crabs in United States, accounting for about 50% of the nation's blue crab harvest (Miller et al 2011). Economically, blue crab is the largest commercial fishery in Chesapeake Bay (Miller et al 2011) with a market value of US$46-103 million annually (Bunnell et al 2010).…”
Section: Background On the Chesapeake Bay Blue Crab Fisherymentioning
confidence: 99%
“…Currently the crab fishery is closed from November or December until March or April of the following year, depending on jurisdiction. In recent years, the management strategy has leaned towards protecting female crabs using a shortened season and short within-season closures for female crabs (Bunnell et al 2010;Miller et al 2011). Size limits vary by jurisdiction, season, and market category.…”
Section: Background On the Chesapeake Bay Blue Crab Fisherymentioning
confidence: 99%
See 1 more Smart Citation
“…Economically, blue crab support important commercial and recreational fisheries in many Atlantic estuaries (Bunnell et al 2010). As a result, management agencies along the eastern United States have collected fishery-independent and fisherydependent data on crabs within their corresponding jurisdictions over a long period of time.…”
Section: Objectivesmentioning
confidence: 99%
“…Several authors have suggested that the blue crab Callinectes sapidus is one species in which this occurring (Hines et al 2003;Jivoff et al 2007;Ogburn et al 2014). The blue crab supports one of the highestvalued commercial fisheries in Chesapeake Bay, with exvessel landings valued at around US$73 million annually (Bunnell et al 2010). Declines in harvest in the 1990s and 2000s caused concern about recruitment overfishing.…”
mentioning
confidence: 99%